Snooping helices: The elastic path finding algorithm of growing hyphae - Antoine Rittaud; Elodie Couttenier; Sophie Bachellier-Bassi; Christophe d’Enfert; Igor M. Kulić; Catherine Villard (Proceedings of the National Academy of Sciences, 2026)
How living organisms utilize physical mechanisms to sense their environments and make informed decisions is an open question at the interface of biology and physics. In filamentous organisms like fungal hyphae, the decisions are taken by their growing tip cells and later imprinted onto the rest of the multicellular filament. Here we report on the growth and pathfinding of hyphae from the opportunistic fungal pathogen Candida albicans , whose ability to cross intestinal epithelial layers is associated to severe systemic infections in humans. It has been sporadically reported that C. albicans ’s hyphae display helical growth inside or on top of agar gels, helicity turning in the latter case into two-dimensional oscillatory shapes. We provide an extended description of oscillatory C. albicans hyphal growth modalities, revealed under various physical confinements thanks to the use of dedicated microfluidic devices and quantitative time-lapse imaging-based analysis. These include sudden sliding events accompanied by curvature switching of the tip portion, resulting in a final oscillatory morphology of the entire filament, and stable curved tips moving against vertical microfluidic channel’s walls. These behaviors are unified under the formalism of growing squeezed helices, in which the final hyphal curved shapes result from an elastic energy minimization of a spatially confined helical portion at the tip followed by a continuous solidification front. Ultimately, the combination of our experimental results and theoretical framework provides an insight into the penetration strategy of C. albicans hyphae, which is essential for the virulence of this fungal microorganism.